INEQUALITY ANALYSIS OF EDUCATION AND ECONOMIC DEVELOPMENT: EDUCATION MANAGEMENT IN INDONESIA - Siti Nurjanah (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2016)
In the end of 2015 is the time for Indonesia to enter the ASEAN Economic Community (AEC) that will integrate with 10 Southeast Asia countries. AEC itself is expected can bring Indonesian economy to be better by expanding the market share. The applicability of AEC not only affects the free trade sectors, but also makes a various workers from ASEAN countries can compete to fill a variety sectors across the ASEAN countries. To be able to compete with other ASEAN countries, Indonesia must have qualified human resources. One of the ways that could be done is through the development of education in Indonesia in order to make high quality human resources. Meanwhile there are still a lot of inequality in Indonesia, both educational inequality and economic inequality itself. This study aims to determine the inequality of education and economic development within the framework of the preparation of AEC. The research methods used are descriptive statistics and statistical inference to know the relationships between the variables. The variables are Gross Enrolment Ratio (GER) and Net Enrolment Ratio (NER), Dropout Rate, Natioal Exam Score, and the Literacy Rate, on the other variables: School Operational Assistance, government expenditure in education sector, Specific Allocation Funds of education, deconcentration fund, GDRP per capita, School-Pupil Ratio, Teacher-Pupil Ratio, and the Teachers' Competency Test. The study was conducted in 33 provinces in Indonesia in 2012-2013. From the results of the estimation using Eviews 7 software, are known that GER inequality, Dropout and Literacy rate inequality variable influenced by economic inequality and education inequality in different directions.